Phosphorus alleviation of nitrogen‐suppressed methane sink in global grasslands - Lihua Zhang; Fenghui Yuan; Junhong Bai; Hongtao Duan; Xueying Gu; Longyu Hou; Yao Huang; Mingan Yang; Jin‐Sheng He; Zhenhua Zhang; Lijun Yu; Changchun Song; et al. (Ecology Letters, 2020)
Grassland ecosystems account for more than 10% of the global CH 4 sink in soils. A 4‐year field experiment found that addition of P alone did not affect CH 4 uptake and experimental addition of N alone significantly suppressed CH 4 uptake, whereas concurrent N and P additions suppressed CH 4 uptake to a lesser degree. A meta‐analysis including 382 data points in global grasslands corroborated these findings. Global extrapolation with an empirical modelling approach estimated that contemporary N addition suppresses CH 4 sink in global grassland by 11.4% and concurrent N and P deposition alleviates this suppression to 5.8%. The P alleviation of N‐suppressed CH 4 sink is primarily attributed to substrate competition, defined as the competition between ammonium and CH 4 for the methane mono‐oxygenase enzyme. The N and P impacts on CH 4 uptake indicate that projected increases in N and P depositions might substantially affect CH 4 uptake and alter the global CH 4 cycle.